Comparative Study on the Applicability of Analytical and Experimental Methods in the Analysis of the Safe Use of Rail Tankers Carrying Petroleum Products Under Pressure - Florescu Virgil; Rece Laurențiu; Mocanu Ștefan; Legendi Amelitta (Romanian Journal of Transport Infrastructure, 2018)
The safety of railways has been and remains a critical topic. Whether it is infrastructure or rolling stock, the issue of safety is a permanent concern of the utmost importance, being reflected in the efficiency of any transport system.